2015
DOI: 10.1039/c5nj00856e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of oligo-closo-dodecaborates by Hüisgen click reaction as encapsulated agents for the preparation of high-boron-content liposomes for neutron capture therapy

Abstract: High-boron-content compounds, 8, 10, and 13, were designed and synthesized as boron agents encapsulated in liposomes by the Hüisgen click cycloaddition of closo-dodecaborate-containing azides and alkynes. These compounds have relatively low cytotoxicities and their GI 50 values for B16, CT26, and HeLa cells are higher than 0.14 mM, indicating toxicities similar to that of BSH. High-boron-content liposomes were prepared using 13, which has the largest number of boron atoms in a molecule among the synthesized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…To date, numerous boron-containing analogues including amino acids, 6 biochemical precursors of nucleic acids, 7 carbohydrates, 8 amines, 9 porphyrins, 10 peptides, 11 liposomes, 12 and monoclonal antibodies have been developed. 13 However, most of them do not satisfy the above criteria for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous boron-containing analogues including amino acids, 6 biochemical precursors of nucleic acids, 7 carbohydrates, 8 amines, 9 porphyrins, 10 peptides, 11 liposomes, 12 and monoclonal antibodies have been developed. 13 However, most of them do not satisfy the above criteria for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3C shows that the molecules of 3 in the liposomes were stable for one week at ambient temperature, as evidenced by the lack of any peaks corresponding to 2,6-dimethylphenylboronic acid (5) or pinacol. It is suggested that the reason for the stability of 3 is that the methyl groups in both of the ortho positions of the phenyl ring and in pinacol protect the boronate ester against attack by water (Fig.…”
mentioning
confidence: 97%
“…3B). The 1 H NMR spectrum of LMI3 did not contain any peaks belonging to 2,6-dimethylphenylboronic acid (5) or the pinacol formed by the hydrolysis of 3 (Fig. 3A and 3B, blue circles).…”
mentioning
confidence: 98%
See 2 more Smart Citations